Clinical analysis of 45 cases of perforation were identified during endoscopic retrograde cholangiopancreatography procedure - Miao, Yin-Shui; Li, Yuan-Yuan; Cheng, Bo-Wen; Zhan, Yan-Fang; Zeng, Sheng; Zhou, Xiao-Jiang; Chen, You-Xiang; Lv, Nong-Hua; Li, Guo-Hua (Frontiers in Medicine, 2022)
Abstract Aim: To analyze the outcome of forty-five patients with endoscopic retrograde cholangiopancreatography related perforation . Methods: We retrospectively reviewed all 45 patients with ERCP-related perforation between January 2003 and December 2017, and observed the location and causes of perforation, treatment strategies and mortality. Results: Twenty thousand four hundred and seventy-nine cases had been received ERCP procedure from January 2003 to December 2017 in our digestive endoscopy center. Forty-five cases suffered from ERCP-related perforation. The incidence of ERCP-related perforation was 0.22%. Twenty-six cases had a peri-ampullary perforation, fifteen cases had a duodenal wall perforation, one case had a fundus perforation, one case had a residual gallbladder duct perforation, one case had a papillary diverticulum perforation, and one case had a intrahepatic bile duct perforation. Six patients with duodenal peroration received surgery, and others received conservative treatment. One patient with a duodenal perforation and a ERCP-related pancreatitis died of heart failure, and others all recovered. The mortality was 2.2%. Conclusions: Endoscopic closure is seen as the first method for treating Stapfer type I perforations in the early phase, surgery is seen as a remedial method when local treatment was failed. The Stapfer II to IV perforations can recover by conservative treatment. Key Words: Endoscopic retrograde cholangiopancreatography(ERCP), Evaluation ,Perforation, Strategy.